Spatiotemporal evolution of ecological vulnerability on the Loess Plateau - Xianqi Zhang; Yupeng Zheng; Yang Yang; He Ren; Jiawen Liu (Ecological Indicators)
The Loess Plateau, located in the northwest of China, is one of the country’s most ecologically fragile regions and a significant source of sediment transported by the Yellow River. Given its ecological importance, a comprehensive assessment of its vulnerability is essential for informing sustainable development initiatives. This study evaluates the ecological vulnerability of the Loess Plateau and aims to provide a theoretical basis for promoting long-term ecological restoration in the region. The “Sensitivity-Resilience-Pressure” (SRP) model was employed to select indicators for assessing ecological vulnerability, while an improved fuzzy analytic hierarchy process (IFAHP) was used to determine the relative weights of these indicators. Using GIS-based overlay analysis, an ecological vulnerability index was calculated, enabling the assessment of spatiotemporal changes and identification of key influencing factors. The results indicate a decreasing trend in ecological vulnerability over the past three decades, with vulnerability levels showing a distinct northwest-to-southeast gradient. Significant spatial variation was observed, with the highest levels of ecological vulnerability concentrated in Inner Mongolia, northern Shaanxi, Ningxia Hui, and Gansu provinces. Vegetation coverage, net primary productivity, and precipitation emerged as the primary drivers of these spatiotemporal changes, with notable interactions between these factors. The findings offer valuable insights for guiding ecological restoration efforts and supporting sustainable management strategies for the Loess Plateau.